Aunt Dimity & the king's ransom [compact disc, unabridged] - Atherton, Nancy (Atherton, Nancy. Aunt Dimity series., 2018)
A dark and stormy night kicks off a ghost chase at the King's Ransom Inn in rural England for Aunt Dimity, Lori Shepherd, and Lori's new friend, Bishop Smallwood.